Novel Genetic Triggers and Genotype–Phenotype Correlations in Patients With Left Ventricular Noncompaction. (August 2017) - Miszalski-Jamka, Karol; Jefferies, John L.; Mazur, Wojciech; Głowacki, Jan; Hu, Jianhong; Lazar, Monika; Gibbs, Richard A.; Liczko, Jacek; Kłyś, Jan; Venner, Eric; Muzny, Donna M.; Rycaj, Jarosław; et al.
Abstract : Background—: Left ventricular noncompaction (LVNC) is a genetically and phenotypically heterogeneous disease and, although increasingly recognized in clinical practice, there is a lack of widely accepted diagnostic criteria. We sought to identify novel genetic causes of LVNC and describe genotype–phenotype correlations. Methods and Results—: A total of 190 patients from 174 families with left ventricular hypertrabeculation (LVHT) or LVNC were referred for cardiac magnetic resonance and whole-exome sequencing. A total of 425 control individuals were included to identify variants of interest (VOIs). We found an excess of 138 VOIs in 102 (59%) unrelated patients in 54 previously identified LVNC or other known cardiomyopathy genes. VOIs were found in 68 of 90 probands with LVNC and 34 of 84 probands with LVHT (76% and 40%, respectively; P <0.001). We identified 0, 1, and ≥2 VOIs in 72, 74, and 28 probands, respectively. We found increasing number of VOIs in a patient strongly correlated with several markers of disease severity, including ratio of noncompacted to compacted myocardium ( P <0.001) and left ventricular ejection fraction ( P =0.01). The presence of sarcomeric gene mutations was associated with increased occurrence of late gadolinium enhancement ( P =0.004). Conclusions—: LVHT and LVNC likely represent a continuum of genotypic disease with differences in severity and variable phenotype explained, in part, by the number of VOIs and whether mutations are present in sarcomeric or nonsarcomeric genes. Presence of VOIs is common in patients with LVHT. Our findings expand the current clinical and genetic diagnostic approaches for patients with LVHT and LVNC. Abstract : Supplemental Digital Content is available in the text.